Beach-cast and drifting seaweed wrack is an important resource for marine and terrestrial macroinvertebrates in high latitudes. (May 2023) - Ulaski, Brian P.; Sikes, Derek S.; Konar, Brenda
Abstract: Seaweeds are foundation species across near-subtidal and intertidal zones, including when detached and free-floating and then cast ashore as wrack. Wrack is sometimes removed by humans for aesthetics or to be used as fertilizer. The study of wrack as an important habitat and resource for macroinvertebrates in high latitudes has been limited. To determine which taxa might be impacted when wrack is removed, the composition and relative abundance of macroinvertebrates were quantified monthly and compared in areas with and without wrack in Kachemak Bay, Alaska. Relationships were assessed between macroinvertebrates and wrack line (tidal height, moisture content, seaweed biomass) and beach characteristics (wave exposure, beach slope, substrate types). Approximately 47, 000 animals were counted and a total of 87 taxa were identified from beach-cast wrack, drifting wrack, and bare sediment habitats. Macroinvertebrate communities within beach-cast wrack and bare sediment habitats were significantly different. Beach-cast wrack generally had more terrestrially-derived animals, especially Coleoptera and Diptera. Bare beach sediment was predominantly occupied by Enchytraeida (annelids). Macroinvertebrate communities were most strongly influenced by seaweed biomass and tidal height of the wrack line. Beach-cast wrack and bare sediments were also compared to drifting wrack in shallow, nearshore waters. Drifting wrack was different and generally occupied by more marine-derived animals, especially Amphipoda, Gastropoda, Mytilida, and Polychaeta. Ecological succession in decaying beach-cast wrack was documented, with decomposers (e.g., Amphipoda and Diptera) being early colonizers, and predators (e.g., Coleoptera and Hymenoptera) arriving later. Understanding the importance of this unique and ecologically important habitat to macroinvertebrates is essential, as removals and reductions in wrack availability could influence macroinvertebrate community structure, higher trophic level consumers, and key ecological processes on beaches. This study is the first direct investigation into seaweed wrack-associated macroinvertebrate communities in a sub-Arctic system. Highlights: Investigation of wrack macroinvertebrate communities in a sub-Arctic system. Select wrack characteristics correlate with macroinvertebrate community composition. Taxonomic grouping and feeding guild successional stages in beach-cast wrack.